Micromamíferos, cambio climático e impacto antrópico: Â¿Cuánto han cambiado las comunidades del sur de América del Sur en los últimos 500 años? - Teta, Pablo; Formoso, Anahí; Tammone, Mauro; de Tommaso, Daniela C.; Fernández, Fernando J.; Pardiñas, Ulyses F. J. (THERYA, 2014)
Introduction: The last 500 years of the historical era, an interval that corresponds to the concerted dispersal of European explorers, traders, and colonists around the globe, has witnessed the global disappearance of 90 mammal species. Besides the known cases of biological extinctions, this time period was also characterized by the regional extirpations of specialized taxa and by the expansion and population growth of some opportunistic species. Several lines of evidence suggest that the current configuration of small mammal communities -i. e. richness (number of species) and diversity (distribution of species abundance)- in southern South America would have been generated in the period after the arrival of Europeans ca. 1500 AD. In this study, we reviewed the fossil record for small rodents and marsupials during the last 500 years, with emphasis on the Pampean and Patagonian regions. Based on these findings, we offer some considerations concerning the biogeography and conservation of these species. Methods: Micromammals from archaeological and paleontological sites have provided considerable information on environmental conditions during the Quaternary in South America. In this work, we reviewed several micromammal fossil samples, mostly generated by the trophic activity of owls. The use of this kind of data involves some extrinsic and intrinsic biases that must be considered at the time to study the diversity of past communities, such as the bird involved on the accumulations, its hunting techniques, the time of the year, the size and behavior of the prey species, etc. For this work, we compared the fossil samples with more than 700 owl pellet assemblages of the same geographical areas. Results: Richness and diversity of small mammal communities was higher prior to the deepest human impact (> 0.5 ka), showing a pronounced drop in both parameters to the present. The regional extinction of some cricetid rodents and small marsupials was recorded, both in the Pampean (e. g. Bibimys torresi,Pseudoryzomys simplex) and in the Patagonian regions (e. g. Euneomys mordax, Lestodelphys halli, Tympanoctomys kirchnerorum), as well as the biological extinctions of the bat Desmodus cf. D. draculae and the cavy Galea tixiensis in the Pampas. At this same time, opportunistic species (e. g. Calomys spp.,Oligoryzomys longicaudatus) showed a dramatic increase of their populations, especially in the most extensively disturbed areas. Discussion and conclusions: In the last 500 years, significant variations occurred in the micromammal assemblages of southern South America. These changes included the dispersion and increase (in some cases extensive) of some specialized species and the regional extinctions of others, involving hundreds to thousands of kilometers of distributional extent. We suggest that the changes produced by livestock and agriculture have caused extensive habitat uniformity which was beneficial for some opportunistic taxa (e. g. Calomys spp., Oligoryzomys longicaudatus), facilitating their dispersion and allowing the increase of their populations. Anthropic disturbances also include the extensive use of fire, urbanization, and introduction of exotic forbs and grasses. Of about 46 species rodents considered as Least Concern by the IUCN and with fossil record for the last 500 years, 23 (50 %) have experienced drastic reductions in their range or abundance during the Late Holocene. At least nine taxa are completely extinct, including one marsupial, one bat and seven rodents. Similar phenomena are recorded in other areas of the Southern Hemisphere, both in continental and island contexts. This evaluation of the fossil record highlights the need to evaluate more carefully the status of some species with supposedly stable populations, but which are likely to be affected by future extensive changes in their environments (e. g. mining, expansion of the agricultural frontier). Key words: Argentina, Didelphimorphia, extinctions, small mammals, Rodentia, Sigmodontinae.